2017
DOI: 10.1007/s13167-017-0090-x
|View full text |Cite
|
Sign up to set email alerts
|

The discovery of the Flammer syndrome: a historical and personal perspective

Abstract: This review describes the clinical and basic research that led to the description of Flammer syndrome. It is narrated from a personal perspective. This research was initiated by the observation of an increased long-term fluctuation of visual fields in a subgroup of glaucoma patients. As these patients had strikingly cold hands, peripheral blood flow was tested with a capillary microscopy, and vasospastic syndrome (VS) was diagnosed. Further studies on these patients revealed frequently weakened autoregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 272 publications
0
49
0
7
Order By: Relevance
“…Previous studies that examined the role of vascular function in glaucoma pathophysiology suggested that vasospasm, systemic hypotension, angiographic vascular perfusion defects, and alterations in blood flow parameters may result in or be a result of reduced vascular perfusion in the optic nerve head and/or retina consequently leading or at least contributing to glaucoma onset and progression [4,[28][29][30][31]. Some authors even regard normal tension glaucoma as an ocular manifestation of a systemic vascular dysfunction, as reflected in the so called Flammer syndrome [32,33]. Other research groups found retinal vascular abnormalities in normal-tension and high-tension glaucoma patients, which include narrowing of retinal blood vessels, optic disc hemorrhage, and reduction of blood vessel density [12,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that examined the role of vascular function in glaucoma pathophysiology suggested that vasospasm, systemic hypotension, angiographic vascular perfusion defects, and alterations in blood flow parameters may result in or be a result of reduced vascular perfusion in the optic nerve head and/or retina consequently leading or at least contributing to glaucoma onset and progression [4,[28][29][30][31]. Some authors even regard normal tension glaucoma as an ocular manifestation of a systemic vascular dysfunction, as reflected in the so called Flammer syndrome [32,33]. Other research groups found retinal vascular abnormalities in normal-tension and high-tension glaucoma patients, which include narrowing of retinal blood vessels, optic disc hemorrhage, and reduction of blood vessel density [12,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A basic demographic questionnaire probed the age, gender, education level, working status, living conditions, and economic status. We selected physiological questions from the (non-standardized) FS checklist to count FS signs and symptoms which are believed to be associated with primary VD (courtesy of Dr. Flammer and Dr. Konieczka, University Eye Clinic Basel, Switzerland, 51) such as cold hands and cold feet, low blood pressure, and reduced thirst [24].…”
Section: Questionnaires and Visual Field Testsmentioning
confidence: 99%
“…One possibility is endotheliopathy of local microvessels due to vascular dysregulation (VD), which reduces (but not stop) oxygen delivery [23][24][25][26][27][28] to levels which are sufficient for cell survival, but insufficient for sustained firing of action potentials. VD is a problem not only for the eye (e.g., in normal tension glaucoma [23,24]) but also for the brain and other organs, leading to a cluster of symptoms and signs such as cold hands or feet, hypotension, diffuse visual field defects, and/or elevated oxidative stress, collectively described by the "Flammer syndrome" (FS) [29][30][31][32][33][34][35]. Furthermore, there are additional FS signs at different levels, including the hormonal (increased cortisol and endothelin-1), physiological (increased sensitivity to pain and drugs, lack of thirst, slim body shape), and psychological levels.…”
Section: Introductionmentioning
confidence: 99%
“…Diesbezüglich hat die Forschungsgruppe in Basel (Schweiz) um Josef Flammer die Vorreiterrolle gehabt [26 -31]; bald danach jedoch haben andere Forschungsgruppen ebenfalls einen wesentlichen Beitrag auf dem Feld geleistet [32,33]. Endothelin stellt ein wesentliches Puzzleteil der Pathophysiologie des Flammer-Syndroms dar [34,35].…”
Section: Endothelin Im Augeunclassified